EPR Study of Freezing Effect on Structural-Functional State of Mitochondrial Membrane - Nardid, O. A. (Problems of Cryobiology and Cryomedicine, 2009)
Structure and electron transport function of rat liver mitochondria membranes have been studied by EPR method of spin probes. It is established that at single rapid freezing of organelles down to –196°C there is an increase in the looseness of membranes of mitochondria without its structural changes, affecting the condition of proteins of electron transfer chain. Two-fold rapid freezing of suspension of mitochondria results in significant damage of membrane structural organization, inducing the disappearing of thermotropic structural transition in the range of 10°C.